Victimization among Justice-Involved Youth with Behavioral and Learning Needs. - Hayes, Brittany E.; Johnson, Shelley; Koetzle, Deborah; Wolff, Kevin T.; Baglivio, Michael T. (Criminal Justice & Behavior, 2026)
The current study investigates the association between behavioral and learning needs and victimization among a sample of justice-involved youth. Drawing from a large data set of adolescents involved in the justice system, bivariate and multivariable analyses explore how behavioral and learning needs are associated with victimization, including trauma, neglect, and violence exposure. Youth with justice involvement who have behavioral and learning needs exhibit higher victimization rates compared to their peers without such needs. Behavioral needs were significantly associated with increased trauma and violence exposure. Results highlight the need for institutions to develop protective measures to mitigate victimization risk among vulnerable populations.